1972
DOI: 10.1149/1.2404370
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Infrared and Activation Analysis Results in Determining the Oxygen and Carbon Content in Silicon

Abstract: The oxygen and carbon content of several silicon single crystals have been measured using 8He activation techniques and are compared with values determined from infrared absorption measurements. The oxygen and carbon content of these crystals as determined from the activation analysis ranged from <0.05 to 28 ppm and <0.05 to 7 ppm, respectively. The infrared absorption measurements gave results that agreed with the activation analysis to within ~40%.Infrared absorption spectrophotometry has been used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…It is noted that [128,129] as well as [130,131] contain the same data respectively, so that only one set of each was taken into account. No explicit data are given by [132][133][134][135][136][137][138]. The available data points are presented in Fig.…”
Section: The Phases (Si) and Liquid: Oxygen Solubilitymentioning
confidence: 99%
“…It is noted that [128,129] as well as [130,131] contain the same data respectively, so that only one set of each was taken into account. No explicit data are given by [132][133][134][135][136][137][138]. The available data points are presented in Fig.…”
Section: The Phases (Si) and Liquid: Oxygen Solubilitymentioning
confidence: 99%
“…Numerous conversion factors have been reported in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Numerous conversion factors have been reported in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It is well known that the addition of oxygen to a CF4 discharge dramatically increases the etch rates of both Si and SiO2 (1-5). One proposed explanation for this increase is that the oxygen combines with fluorocarbons in the discharge to keep the surface free from carbonaceous deposits, thereby leaving surface sites available to be etched (2). However, it has been suggested that this effect alone cannot be entirely responsible for the increase and that an enhanced production of fluorine atoms is probably initiated by a reaction of oxygen with radicals in the plasma (2).…”
Section: Discussionmentioning
confidence: 99%